Genetic and metabolic profiling of individuals with Phelan‐McDermid syndrome presenting with seizures. Issue 1 (27th October 2021) - Jain, Lavanya; Oberman, Lindsay M.; Beamer, Laura; Cascio, Lauren; May, Melanie; Srikanth, Sujata; Skinner, Cindy; Jones, Kelly; Allen, Bridgette; Rogers, Curtis; Phelan, Katy; Kaufmann, Walter E.; et al.
Abstract: Phelan‐McDermid syndrome (PMS) (OMIM*606232) is a rare genetic disorder characterized by intellectual disability, autistic features, speech delay, minor dysmorphia, and seizures. This study was conducted to investigate the prevalence of seizures and the association with genetic and metabolic features since there has been little research related to seizures in PMS. For 57 individuals, seizure data was collected from caregiver interviews, genetic data from existing cytogenetic records and Sanger sequencing for nine 22q13 genes, and metabolic profiling from the Phenotype Mammalian MicroArray (PM‐M) developed by Biolog. Results showed that 46% of individuals had seizures with the most common type being absence and grand‐mal seizures. Seizures were most prevalent in individuals with pathogenic SHANK3 mutations (70%), those with deletion sizes >4 Mb (16%), and those with deletion sizes <4 Mb (71%) suggesting involvement of genes in addition to SHANK3 . Additionally, a 3 Mb genomic region on 22q13.31 containing the gene TBC1D22A, was found to be significantly associated with seizure prevalence. A distinct metabolic profile was identified for individuals with PMS with seizures and suggested among other features a disrupted utilization of main energy sources using Biolog plates. The results of this study will be helpful for clinicians and families in anticipating seizures in these children and for researchers to identify candidate genes for the seizure phenotype. Abstract :